Effect of ultrasonic burst microbubbles on microwave coagulation hemostasis in a pig model of hepatic hemorrhage - Bibo Peng; Shengnan Li; Nong Gao; Zhaojie Guan; Huina Song; Xiangnan Gao; Qu Liu; Lusi He; Jing Guo; Lina An (Scientific Reports)
Abstract To investigate the hemostatic efficacy of ultrasound in flash mode and/or microbubbles-assisted microwave coagulation for active liver hemorrhage. Thirty miniature pigs were randomly divided into five groups. Active hepatic hemorrhage was induced under ultrasound guidance. Treatment groups included microwave ablation (MWA), microbubbles with microwave ablation (MBs + MWA), ultrasound in flash mode with microwave ablation (Flash + MWA), ultrasound in flash mode with microbubbles and microwave ablation (Flash + MBs + MWA), and ultrasound in flash mode with phosphate-buffered saline and microwave ablation (Flash + PBS + MWA). Hemostasis time, blood tests, ultrasound, pathological inspections, and analysis were conducted. The Flash + MBs + MWA group showed the shortest hemostasis time, with 2.25 ± 0.45, 2.42 ± 0.51, and 5.50 ± 0.52 min for diaphragm, gallbladder, and hepatic artery bleeding. Highest blood cell stability and a significantly larger hemostatic lesion range were observed in this group on ultrasound. Pathological analysis revealed varied extents of liver sinus congestion and dilation. The combination of ultrasound contrast microbubbles system and microwave thermal coagulation can effectively treat active hepatic hemorrhage, and microbubbles in ultrasound Flash mode have an enhancing effect on microwave coagulation hemostasis.